Penggunaan Pendekatan Problem Solving Sebagai Upaya Peningkatan Hasil Belajar Matematika Siswa - Mindarti, Mindarti (Journal of Comprehensive Science, 2024)
This research aims to describe the application of a problem solving model to improve learning outcomes for flat shapes and space shapes in class VI students at SD Negeri 3 Jereweh. The problem formulation in this research is how to apply the problem solving model to improve Mathematics learning outcomes in plane figures and geometry in class VI students at SD Negeri 3 Jereweh. This research was conducted in class VI of SD Negeri 3 Jereweh. This research was carried out in two cycles and each cycle was held in two meetings. The subjects were 20 grade VI students at SD Negeri 3 Jereweh, with 9 male students and 11 female students. The data collection techniques used in this research are observation, documentation and tests. Based on the research results, it was concluded that in cycle I it was still considered sufficient with an average of 74.66, so out of 20 students only 12 or 60% of students achieved completeness individually. Student learning outcomes in cycle II were in very good condition with an average of 88.00, and 18 students or 95% of them achieved completeness individually. It can be concluded that applying problem solving can improve the learning outcomes of flat shapes and space shapes in class VI students at SD Negeri 3 Jereweh.